Dictionary of common words in Indian Languages (volume-II) - Lalita Handoo (My University, 2015)
Bilingual and multilingual dictionaries, to a great extent, help in bridging the gap between two or more languages and serve as a very important language learning aid. Central Institute of Indian Languages has brought out a number of bilingual and multilingual dictionaries besides some common vocabularies as an aid to teaching Indian languages as second language.
Keywords: Assamese; Bengali; Gujarati; Hindi; Kannada; Kashmiri; Malayalam; Marathi; Odia; Punjabi; Sindhi; Tamil; Telugu; Urdu